Studi awal material komposit berpenguat serat bambu dengan matriks resin epoksi/hardener sebagai material antipeluru - Harmiansyah; Burmawi; Risky Arman; Rustam Efendi (Badan Kerja Sama Teknik Mesin Indonesia, 2022)
Bulletproof material is used as a bulletproof vest material that functions to protect the human body from the threat of physical attack, especially attacks from firearms. Bulletproof material serves to reduce the kinetic energy of the projectile so it does not hit the bulletproof vest user. The main material in the manufacture of bulletproof material is steel with a high density so that the weight of the bulletproof material is high which causes the user to be unable to move freely. Composite is a material consisting of two or more elements that have good mechanical properties and low density so that it can be used as an alternative to steel for bulletproof materials. The bulletproof material used was reinforced with bamboo fiber with a matrix of epoxy resin/hardener mixture and the addition of 20, 25, and 30 ml ceramic granules, the composite material was tested for ballistics using a variation of the firing range parameter 2; 2.5; and 3 m. Based on the results of ballistic tests, all variations of the addition of ceramic granules were able to reduce the energy of the projectile with a penetration depth of < 1 mm where the kinetic energy of the projectile was 209.83 joule. Based on the macro photo analysis of projectile traces on the bulletproof material, the cracks that occur in the bulletproof material are ductile cracks due to the spread of the cracks to other areas on the surface of the bulletproof material.